Faktor penentu kelangsungan hidup UMKM di Indonesia pasca pandemi Covid-19 - Santi Rimadias (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This study aims to analyze innovation capability, consumer engagement, entrepreneurial orientation, and Muslim religiosity as determining factors for the survival of Micro, Small, and Medium Enterprises (MSMEs) after the Covid-19 pandemic. Muslim MSME entrepreneurs in Indonesia, totaling 78 respondents, were involved in the survey in this study. A structured online questionnaire with a particular scale was used in this study. PLS-SEM was used to analyze the data through SMART-PLS 3.0 software. The study's results reveal that Muslim religiosity positively affects the survival of SMEs (firm survival). Innovation capability has a positive effect on entrepreneurial orientation. Entrepreneurial orientation has a positive effect on consumer engagement. Meanwhile, entrepreneurial orientation and consumer engagement do not affect the survival of MSMEs (firm survival). The implications of this research can be a reference for MSME Muslim entrepreneurs and policymakers related to MSMEs in formulating strategies to build the sustainability of MSME performance after the Covid-19 pandemic.